Acute atrazine intoxication in heifers: Case report and toxicological studies - Marron, Yolanda (2024)
Atrazine is a triazine organochloride herbicide, frequently used in different agricultural activities. Rare acute intoxication with atrazine is reported in production animals, and its metabolism in mammals is unknown. We report a spontaneous case of atrazine acute intoxication in 16.1% animals of a 168-beef heifer herd exposed to the herbicide at a farm located in Buenos Aires province, Argentina. Affected heifers showed different neurological signs and died suddenly, similar to the previous natural atrazine intoxication report. During autopsy, no gross lesions were observed. Different body fluids and tissues samples were collected during postmortem examination. No relevant histopathological findings were observed. High levels of atrazine and its metabolites were detected in different fluids and tissues by ultra-liquid chromatography high performance coupled to triple quadrupole mass spectrometry. These findings suggest ruminal or hepatic metabolization of atrazine in the exposed cattle. This is the first report of quantification and distribution of atrazine and its metabolites in intoxicated mammals providing relevant information for diagnostic purposes.